2004
DOI: 10.1111/j.1526-4610.2004.04198.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Disturbing Migraine Aura With Lamotrigine: An Open Study

Abstract: Lamotrigine should be considered in clinical practice for the preventive treatment of selected patients with disturbing migraine auras. Lamotrigine seems worthy of a controlled trial as prophylaxis of migraine aura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 25 publications
(44 reference statements)
3
50
1
1
Order By: Relevance
“…This consideration addressed us in the past to use in these three of our BM patients lamotrigine, effective drug in preventing migraine aura and cortical spreading depression and in reducing migraine headache frequency [4]. After open study by Pascual et al [5] on lamotrigine use for the preventive treatment of selected patients with disturbing migraine auras, including those with BM and hemiplegic migraine, no other clinical trials have been reported in the literature. Other anticonvulsant drugs have been tested in BM such as sodium valproate [6] and topiramate in a child population [7] with a good response at both 25 and 100 mg doses.…”
Section: Discussionmentioning
confidence: 99%
“…This consideration addressed us in the past to use in these three of our BM patients lamotrigine, effective drug in preventing migraine aura and cortical spreading depression and in reducing migraine headache frequency [4]. After open study by Pascual et al [5] on lamotrigine use for the preventive treatment of selected patients with disturbing migraine auras, including those with BM and hemiplegic migraine, no other clinical trials have been reported in the literature. Other anticonvulsant drugs have been tested in BM such as sodium valproate [6] and topiramate in a child population [7] with a good response at both 25 and 100 mg doses.…”
Section: Discussionmentioning
confidence: 99%
“…His headaches began at age 9 while under the care of pediatric neurologist in Charleston, West Virginia. His condition worsened after a motor vehicle accident, particularly the headaches of which he had [3,4] bad ones per week. Neurontin, 400 mg, two tablets three times per day and 400 mg of felbamate daily did not reduce the headaches in number or in severity nor did the seizures changed.…”
Section: Casementioning
confidence: 99%
“…Thus, a ketogenic diet has been found effective in preventing the migraines and the ensuing epilepsy [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of fi ndings from the two studies showed that response rates for 2-hour pain relief, 2-hour pain free and SPF were higher for the patients receiving treatment from the PCPs than those treated by the neurologists ( fi g. 1 ) [19,20] . These results suggest that the patients receiving therapy from the neurologists are more diffi cult to treat than those who are seen by the PCPs.…”
Section: Spanish and German Postmarketing Surveillance Studiesmentioning
confidence: 99%
“…Two multicenter, open-label observational PS studies of the effi cacy and tolerability of almotriptan 12.5 mg in the acute treatment of migraine have been conducted in Spain [19,20] . The fi rst study recruited patients receiving headache treatment from neurologists, and approximately 1,000 were analyzed for effi cacy (intent-to-treat analysis).…”
Section: Spanish and German Postmarketing Surveillance Studiesmentioning
confidence: 99%